MORALITAS, DINAMIKA, DAN KEBEBASAN MANUSIA MENURUT AL-QUR’AN PERSPEKTIF KONSELING ISLAM - Afnilas Wati; Risman Bustamam (JURNAL KONSELING GUSJIGANG, 2020)
This article aims to describe morality, dynamics and human freedom according to the Qur'anic perspective of Islamic counseling.Humans are social creatures, who need help from others in their lives.In order to establish good relationships with people who are around him, these people must pay attention and consider many things, including moral attitude or morality, dynamics and freedom.The novelty of the article is to examine morality, dynamics and human freedom according to the Qur'an.The results of this study are in the perspective of Islamic counseling, the role of the counselor is needed in maintaining and enhancing these three things in his client, so that clients get happiness in his life both in the world and the hereafter.The final conclusion of the study results is that everything that is done by humans in this world will be accounted for by humans themselves both in the world and in the future.